Stability analysis of two-terminal HVDC transmission systems using SISO open-loop gains - Tan, Shangning; Liu, Junliang; Du, Xiong; Yang, Hongjun; Cao, Yuelong (Frontiers in Energy Research, 2023)
The AC and DC port of a three-phase voltage source converter have multiple frequency electrical parameters, which makes the HVDC transmission system with the converters present multiple input multiple output (MIMO) characteristics. The generalized Nyquist criterion of the MIMO model is often used to analyze the system stability. However, the stability margin and the oscillation frequency band are difficult to capture using the generalized Nyquist criterion. To solve the above problems, this paper takes the two-terminal HVDC transmission system as the research object, and derives the SISO model. Then, a method for analyzing the system stability is proposed by using the SISO open-loop gains. Finally, the key modules and parameters affecting the system stability are identified based on the stability margin. which provides theoretical support for the design of system parameters. The established model and the proposed analysis method are verified in time domain simulations.